Numerical study of slope protected by rockfill and shredded tyre mixture gabion wall - A. C., Ainul Mardziah; Amizatulhani, Abdullah (2019)
Abundance of discarded scrap tyre in Malaysia demand diverse recycling products, in order to reduce its environmental pollutions and simultaneously the negative aftermaths to society and future generation. Hence, this paper is established to investigate the potential of tyre derived geo-material as rock fill alternative in conventional gabion type retaining wall, replacing a portion of the non-renewable rock fill. 4-tier scrap tyre gabion wall (STG wall) in terraced position with various scrap tyre ratio from total gabion rock fills volume are modelled to retain a 5.0m height of existing failed slope. The model are analysed by finite element method in Slope/W 2007 software (Morgenstern-Price analysis method) to assess overall stability of the gabion wall and factor safety (FOS) of the treated slope. From this study, higher FOS is acquired when STG wall incorporated into the failed slope compared to using conventional gabion wall.